GAMBARAN PERILAKU PENDERITA TUBERKULOSIS DALAM UPAYA KEPATUHAN MINUM OBAT DI PUSKESMAS TANJUNG MORAWA - Lumban Tobing, Paul Saut Marganda; Sinurat, Suryati; Swastikanti, Ruth Aktrisari; Juliana, Deska; Surmanto, Boy; Cristiana, Eva; Pandia, Andre Kornelius (Universitas Methodist Indonesia, 2023)
Based on data from the Global Tuberculosis Report 2020, it is known that 1.4 million people died from tuberculosis. Indonesia is ranked third in the world with 845,000 cases. It is estimated that as many as 24,000 cases of drug-resistant tuberculosis each year, known as Multi Drug Resistant (MDR). An initial survey conducted in the work area of the UPT Puskesmas Tanjung Morawa found that the complete treatment rate for all tuberculosis cases was 60%. One of the indicators of the success of the TB eradication program is drug compliance, so research was conducted using descriptive methods with a cross-sectional approach to see the behavior of tuberculosis patients in efforts to adhere to taking medication. The results obtained in the form of a description of the level of knowledge, attitudes and actions of TB patients who have a high level of compliance in the respondents of this study.